2023
DOI: 10.1111/1365-2656.14012
|View full text |Cite
|
Sign up to set email alerts
|

Integrated community models: A framework combining multispecies data sources to estimate the status, trends and dynamics of biodiversity

Elise F. Zipkin,
Jeffrey W. Doser,
Courtney L. Davis
et al.

Abstract: Data deficiencies among rare or cryptic species preclude assessment of community‐level processes using many existing approaches, limiting our understanding of the trends and stressors for large numbers of species. Yet evaluating the dynamics of whole communities, not just common or charismatic species, is critical to understanding and the responses of biodiversity to ongoing environmental pressures. A recent surge in both public science and government‐funded data collection efforts has led to a wealth of biod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 132 publications
0
12
0
Order By: Relevance
“…Previous studies have shown that IDMs perform better than single‐dataset models in estimating state variable parameters and prediction accuracy of new datasets (Pacifici et al 2017, Miller et al 2019, Doser et al 2022, Strebel et al 2022). Miller et al (2019) noted that IDMs present opportunities to model community dynamics and diversity from multiple datasets, and Zipkin et al (2023) presented an integrated community model to explore such opportunities. Our IDM shares information among species and provides estimates for parameters at both species and community levels (Zipkin et al 2023).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown that IDMs perform better than single‐dataset models in estimating state variable parameters and prediction accuracy of new datasets (Pacifici et al 2017, Miller et al 2019, Doser et al 2022, Strebel et al 2022). Miller et al (2019) noted that IDMs present opportunities to model community dynamics and diversity from multiple datasets, and Zipkin et al (2023) presented an integrated community model to explore such opportunities. Our IDM shares information among species and provides estimates for parameters at both species and community levels (Zipkin et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Miller et al (2019) noted that IDMs present opportunities to model community dynamics and diversity from multiple datasets, and Zipkin et al (2023) presented an integrated community model to explore such opportunities. Our IDM shares information among species and provides estimates for parameters at both species and community levels (Zipkin et al 2023). Our work provides further advancements in such integrated community models by providing an IDM that combines data from different taxonomic levels to estimate alpha diversity in a community.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations